Paradoxes of Pain: A Dialogue between Plato and Contemporary Phenomenology - Bernat Morales Torres (Azafea: Revista de Filosofía, 2020)
The paper presents a dialogue, between contemporary phenomenology and Plato, on the nature and complexity of pain. Taking as a departure point D. Leder’s article «The experiential paradoxes of pain», the article delves into the essentially liminal character of pain and focusses afterwards in two paradoxes that this experiences reveals. The first one is the one that describes pain as a sensation and also as an interpretation; the second one is the one that describes pain as a destructive and also productive experience. Throughout the article we will see that the Platonic approach, although being much more holistic (in the sense of combining always the persona, ethical, political and also cosmological perspective), is not far away from the phenomenological one. That both approaches try to set limits and to describe an experience that escapes all limitations and determinations.